Optimizing aerosol jet printing process of silver ink for printed electronics - Agarwala, Shweta (2017)
Aerosol jet is an additive manufacturing technique that writes electronic inks directly onto the surface. The process has great potential for printed electronics as it is non-contact method that works well with variety of materials- metals, insulators, semiconductors, epoxy and encapsulation materials for conformal writing. This paper explores the effect of some parameters like ultrasonic power and atomizer flow on overall print quality, thus establishing a process window.